Mining and agriculture in the Mashavera valley (South-eastern Georgia) – A land use conflict with severe consequences - B. Kalandadze; T. Hanauer; P. Felix-Henningsen; T. Urushadze; E. Narimanidze; Steffens, D. (ՀՀ ԳԱԱ հրատ.)
The fertile irrigated soils of the Mashavera valley, Georgia, have high agricultural yield potential. The river water used for irrigation is polluted with mining waste from a copper and gold mine situated in mountainous region of the middle reaches of Mashavera River. Therefore the actual risk of Cd transfer into the food chain is proven, which affects the local population as well as people in cities up to capital Tbilisi, where crops from the Mashavera valley are sols at the open markets. Վրաստանի Մաշարավա դաշտավայրի բերրի, ոռոգելի հողերը ունեն մեծ գյուղատնտեսական ներուժ: Ոռոգման համար օգտագործվող գետի ջրերը աղտոտված են Մաշարավա գետի միջին հոսանքի տարածքում գնվող ոսկու և պղնձի լեռնա-հանքային արդյունաբերական ձեռնարկության թափոններով: Այդ տարածքում ստացվող սնունդը և կերը գնտվում են ծանր մետաղներով աղտոտման մեծ վտանգի տակ, որն իր հերթին վտանգում է տեղի և Թիֆլիսի բնակիչների առողջությունը: Орошаемые плодородные почвы долины Машавера, Грузия, имеют высокий сельскохозяйственный потенциал. Воды реки используемые для орошения загрязнены отходами горно-добывающей промышленности меди и золота, которая расположены в горном регионе в среднем течении реки Машавера. Существует серьезный риск загрязнения кормов и продуктов питания как для местного населения так и жителей Тбилиси.
Keywords: Biology; Biological Diversity